Voluntary disclosure and company characteristics of Indonesian listed company: comparison of Shariah and non-Shariah compliant company - Nugraheni, Peni; Annuar, Hairul Azlan (2011)
This research attempts to investigate the extent of voluntary disclosure in the annual reports of Shariah compliant companies listed in Indonesian Stock Exchange and compare it with non-Shariah compliant companies. Voluntary disclosures were measured using 30 items of disclosure index developed by Khomsiah (2005). Based on content analysis of 2009 annual report of 55 Indonesian listed companies for each category, the findings revealed that there is statistically significant difference in the quantity and quality of voluntary disclosure value of Shariah and non-Shariah compliant companies. Further, for Shariah compliant companies, the study examined the relationship between voluntary disclosure and company characteristics (i.e. size of company, profitability, type of auditor type of industry, and ownership structure). Company size and type of industry significantly influence the voluntary disclosure while three factors of company characteristics (profitability, type of auditor and ownership structure) are found insignificant.